Critérios para avaliação de desempenho de sistema de geração distribuída de energia elétrica fotovoltaica - Silva Junior, Alcides Pereira da (2024)
The global energy transition process aims to establish a new framework based on renewable and low environmental impact sources, targeting the reduction of greenhouse gas emissions crucial for combating climate change, such as global warming. Besides decarbonization, the energy transition seeks innovations in generating, transmitting, distributing, trading, and consuming electricity. This is evident in the decentralization and digitalization of the electrical sector, seen in individual production (distributed generation) or self-consumption of energy, regulatory and tariff mechanisms, technologies for enhanced energy supply security and efficiency, as well as new business models centered around technologies enabling consumers to be at the forefront of energy policy as energy producers (or prosumers). Among the technological innovations in the energy market, individual electricity generation through photovoltaic devices stands out currently. It is within this context that this research aims to propose criteria for evaluating a photovoltaic distributed generation technological innovation system. For this survey, a systematic literature mapping study was conducted, supported by snowball sampling and content analysis methodologies, which, through a portfolio of 85 articles and deductive and inductive analyses (using MAXQDA software), allowed the coding and categorization of texts related to the analysis model of technological innovation systems: (F1) development and diffusion; (F2) markets and policies; (F3) research: technologies and experimentation; (F4) market formation; (F5) resources; (F6) legitimation: impacts and public opinion; and (F7) positive externalities. This enabled the proposition of 55 analytical criteria to be considered for the evaluation of the photovoltaic distributed generation technological innovation system.